2016
DOI: 10.1371/journal.pone.0146883
|View full text |Cite
|
Sign up to set email alerts
|

Fine-Needle Aspiration Biopsy as a Preoperative Procedure in Patients with Malignancy in Solitary and Multiple Thyroid Nodules

Abstract: BackgroundFine-needle aspiration biopsy (FNAB) is a recognized technique for the basic, preoperative cytological diagnosis of thyroid nodules.Aim of the StudyTo analyze the accuracy of FNAB in the diagnosis of thyroid cancer in patients with solitary and multiple thyroid nodules and to compare the demographic, clinical and pathological characteristics of patients with thyroid carcinoma in solitary and multiple tumors.Materials and MethodsThe case records of 2,403 patients with solitary and multiple thyroid tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 35 publications
1
18
0
1
Order By: Relevance
“…1,2 Typically, cytology smears show papillary configuration, characteristic nuclear features like nuclear grooves and pseudoinclusions, or even psammoma bodies, which if present, are highly suggestive of this diagnosis. Papillary thyroid carcinoma (PTC) is the most common thyroid malignancy and can be readily diagnosed by cytology, thus fine needle aspiration (FNA) is the initial diagnostic procedure of choice.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…1,2 Typically, cytology smears show papillary configuration, characteristic nuclear features like nuclear grooves and pseudoinclusions, or even psammoma bodies, which if present, are highly suggestive of this diagnosis. Papillary thyroid carcinoma (PTC) is the most common thyroid malignancy and can be readily diagnosed by cytology, thus fine needle aspiration (FNA) is the initial diagnostic procedure of choice.…”
Section: Introductionmentioning
confidence: 99%
“…Papillary thyroid carcinoma (PTC) is the most common thyroid malignancy and can be readily diagnosed by cytology, thus fine needle aspiration (FNA) is the initial diagnostic procedure of choice. 2 Biphenotypic thyroid carcinomas, conversely, are not uncommon with anaplastic thyroid carcinoma arising in association with papillary or follicular thyroid carcinoma being the most common example. 1,3 Multiple thyroid malignancies is a rare situation, and accurate diagnosis by FNA has reportedly high false-negative rate reaching up to 69%.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, FNAB has shown less accuracy in the evaluation of multinodular thyroid gland as 2 out of 4 cases with multiple nodular thyroid mass were initially diagnosed as colloid goitre. Kaliszewski et al 28 have shown in their study that the rate of prediction of thyroid cancer by FNAB in the patients with solitary thyroid nodule was three times higher than that in the patients with multiple nodule. This is important as in cases with negative FNAB result, the surgeon may perform a less radical procedure which will require another surgery for complete removal of the remaining thyroid gland.…”
Section: Discussionmentioning
confidence: 92%